Exclusive breastfeeding campaign to prevent stunting at Sinar Kasih Bogor School - Yosi Marin Marpaung; Vania Natasha; Ruth Ruth; Jesita Mintjelin Managge Edam; Mey Lona Verawaty Zendrato (Community Empowerment, 2024)
Stunting is a serious health issue in Indonesia, preventable through exclusive breastfeeding. Initial research among mothers of Sinar Kasih School Bogor students revealed inadequate knowledge, attitudes, and practices regarding exclusive breastfeeding and stunting. This community service aimed to enhance maternal knowledge about exclusive breastfeeding and stunting risk factors. Through interactive lectures and educational media, the program sought to foster correct exclusive breastfeeding practices. Methods included interactive lectures using PowerPoint, leaflets, and teaching aids. Evaluations conducted pre and post-activity measured knowledge increases. Results demonstrated a significant rise in maternal knowledge about exclusive breastfeeding and stunting, enabling mothers to identify stunting risk factors, understand exclusive breastfeeding's importance, and learn breast milk storage.